2010
DOI: 10.1002/art.27700
|View full text |Cite
|
Sign up to set email alerts
|

Anti–U1 RNP antibodies in cerebrospinal fluid are associated with central neuropsychiatric manifestations in systemic lupus erythematosus and mixed connective tissue disease

Abstract: Objective. To determine the significance of anti-U1 RNP antibodies in the cerebrospinal fluid (CSF) of patients with systemic lupus erythematosus (SLE) or mixed connective tissue disease (MCTD) who have central neuropsychiatric SLE (NPSLE).Methods. The frequency of antinuclear antibodies including anti-U1 RNP antibodies in the sera and CSF of 24 patients with SLE and 4 patients with MCTD, all of whom had neuropsychiatric syndromes, was determined using an RNA immunoprecipitation assay and an enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 72 publications
(44 reference statements)
1
68
2
4
Order By: Relevance
“…immunoglobulins (Igs) and cytokines into the CSF, is now considered as an important component in NPSLE development [37][38][39]. Increased CSF levels of Igs, Abs and proinflammatory cytokines, as well as elevated albumin concentration, are indicative of increased BBB's permeability [40][41][42], and have additionally been associated with NP manifestations [40,[43][44][45][46][47].…”
Section: Npsle: Cns Involvement In Human Slementioning
confidence: 99%
“…immunoglobulins (Igs) and cytokines into the CSF, is now considered as an important component in NPSLE development [37][38][39]. Increased CSF levels of Igs, Abs and proinflammatory cytokines, as well as elevated albumin concentration, are indicative of increased BBB's permeability [40][41][42], and have additionally been associated with NP manifestations [40,[43][44][45][46][47].…”
Section: Npsle: Cns Involvement In Human Slementioning
confidence: 99%
“…Sato et al demonstrated that CSF anti-RNP were associated with NPSLE and CNS manifestations in mixed connective tissue disease as a more specific marker of NPSLE than anti-P or anti-NR2 [24]. However, the elevation of CSF anti-RNP was not specific in ACS or diffuse NPSLE, since CSF anti-RNP was also elevated in patients with focal NPSLE, including aseptic meningitis, headache, demyelinating disorder or movement disorder [24].…”
Section: Anti-u1-rnp Antibodiesmentioning
confidence: 99%
“…By contrast, patients diagnosed with SLE and other autoimmune syndromes were included during the production of each of the four classification criteria sets for MCTD (Amigues et al, 1996). Nevertheless, these studies did not included well characterized MCTD cases and rather choose the presence of positive anti-U1 snRNP antibodies as patient inclusion criteria despite knowing these antigens elicit a response in SLE and MCTD subjects (Amigues et al, 1996;Sato et al, 2010;Nagai et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune responses to U1 snRNP specific proteins, including U1Ap, have been described in patients diagnosed with Systemic Lupus Erythematosus (SLE) and Mixed Connective Tissue Disease (MCTD) (de Wildt et al, 1997;Faig and Lutz , 2003;McClain et al, 2004;Sato et al, 2010). In some patient cohorts, anti-U1Ap responses have been reported to be the first anti-U1-snRNP to develop (McClain et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation